2022
DOI: 10.3389/fneur.2022.1029851
|View full text |Cite
|
Sign up to set email alerts
|

Associations of audiometric hearing and speech-in-noise performance with cognitive decline among older adults: The Baltimore Longitudinal Study of Aging (BLSA)

Abstract: BackgroundEstablished associations between hearing loss and cognitive decline were primarily defined by pure-tone audiometry, which reflects peripheral hearing ability. Speech-in-noise performance, which reflects central hearing ability, is more limited in prior literature. We examined the longitudinal associations of audiometric hearing and speech-in-noise performance with cognitive decline.MethodsWe studied 702 participants aged ≥60 years in the Baltimore Longitudinal Study of Aging 2012–2019. Global and dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Lower scores in the present study might be explained by our baseline sample being relatively younger (mean age 51.6 vs. 73.4 25 and 64.1 26 ), since hearing acuity decreases with aging. For mild and moderate to profound HL, previous longitudinal studies generally support our results that objectively measured HL is associated with accelerated cognitive decline in multiple domains 27–31 . Studies examining HL with pure tone audiometry measures generally used a 25 dB threshold to define HL, 27–29 and in the study of Deal et al., 28 only moderate to severe HL (>40 dB) was associated with accelerated cognitive decline.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Lower scores in the present study might be explained by our baseline sample being relatively younger (mean age 51.6 vs. 73.4 25 and 64.1 26 ), since hearing acuity decreases with aging. For mild and moderate to profound HL, previous longitudinal studies generally support our results that objectively measured HL is associated with accelerated cognitive decline in multiple domains 27–31 . Studies examining HL with pure tone audiometry measures generally used a 25 dB threshold to define HL, 27–29 and in the study of Deal et al., 28 only moderate to severe HL (>40 dB) was associated with accelerated cognitive decline.…”
Section: Discussionsupporting
confidence: 83%
“…For mild and moderate to profound HL, previous longitudinal studies generally support our results that objectively measured HL is associated with accelerated cognitive decline in multiple domains. [27][28][29][30][31] Studies examining HL with pure tone audiometry measures generally used a 25 dB threshold to define HL, [27][28][29] and in the study of Deal et al, 28 To our knowledge, incident HL has not been examined before in the context of cognitive change over time. We found that cognitive decline in incident HL was restricted to a change from 6-to 12-year follow-up, without a significant change in the first six years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual patient's decision to elect observation therapy for VS may be affected by their expected hearing outcomes. A heightened risk of hearing loss may even change the decision calculus altogether given the substantial implications of hearing loss on quality of life and health outcomes (38)(39)(40). Continued evaluation of this relationship may prove useful in providing additional information for clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…and sensorineural hearing loss, especially if left untreated, appears to further accelerate cognitive decline. Significant associations were found between hearing thresholds (dB PTA) and cognitive performance [Retrospective: ( 6 , 7 , 9 14 )]; Prospective: ( 5 , 15 , 20 ); Systematic review: ( 7 , 8 ). 1 Starting with a subclinical hearing loss < 25 dB, audiometric hearing loss (pure tone average) was associated with cognitive decline [Subclinical hearing loss ( 10 ), mild hearing loss ( 11 , 12 ), moderate and severe hearing loss ( 5 , 21 )].…”
Section: Introductionmentioning
confidence: 99%